Generation of high energy laser-driven electron and proton sources with the 200 TW system VEGA 2 at the Centro de Laseres Pulsados. (26th April 2019) - Volpe, L.; Fedosejevs, R.; Gatti, G.; Pérez-Hernández, J. A.; Méndez, C.; Apiñaniz, J.; Vaisseau, X.; Salgado, C.; Huault, M.; Malko, S.; Zeraouli, G.; Ospina, V.; et al.
Abstract : The Centro de Laseres Pulsados in Salamanca, Spain has recently started operation phase and the first user access period on the 6 J 30 fs 200 TW system (VEGA 2) already started at the beginning of 2018. In this paper we report on two commissioning experiments recently performed on the VEGA 2 system in preparation for the user campaign. VEGA 2 system has been tested in different configurations depending on the focusing optics and targets used. One configuration (long focal length $F=130$  cm) is for underdense laser–matter interaction where VEGA 2 is focused onto a low density gas-jet generating electron beams (via laser wake field acceleration mechanism) with maximum energy up to 500 MeV and an X-ray betatron source with a 10 keV critical energy. A second configuration (short focal length $F=40$  cm) is for overdense laser–matter interaction where VEGA 2 is focused onto a $5~\unicode[STIX]{x03BC}\text{m}$ thick Al target generating a proton beam with a maximum energy of 10 MeV and temperature of 2.5 MeV. In this paper we present preliminary experimental results.